The Impact of Brand Image, Food Quality, and Product Price Toward Customers Attraction in Restaurant Nelayan Medan - Amanda; Huang, Charlie; Hantanto, Fellicia; Laurensia, Jennetha; Tanata, Vianca (International Journal of Economics, Business Management and Accounting (IJEBMA), 2021)
A normality test will be performed to determine if the data for the variables follows a normal distribution. The purpose is to choose the appropriate statistical method for exploring the relationship between the variables (Rizki & Gustia, 2019). The normality of the data is tested using the sig Kolmogrov-Smirnov statistic. SPSS Statistics 29 was used to run the test, and a significance level of 0.05 was selected. Data can be assumed to be normally distributed if and only if the p-value is greater than.05. In contrast, an abnormal distribution of data is indicated if the value is smaller than 0.05